Scientific Writing Coaching Class for Teachers in Sibolga City - gea, saharman; Aththorick, T. Alief; Lenny, Sovia; Sihombing, Yuan Alfinsyah; Pasaribu, Khatarina Meldawati; Piliang, Averrous Fazlurrahman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Referring to Ministerial Regulation of PAN-RB No. 16 of 2009 on Teacher Functional Status and Credit Score, it is clearly mentioned that one of the key components to apply teacher promotion is scientific writing (KTI). However, in fact, it was found that many teachers were independently constrained, especially in Sibolga City. As a result, the chance to get a higher rank and to be placed would be hampered. In addition, even some teachers are caught up in taking shortcuts by using the third part services to prepare their scientific writing, which of course, are not acceptable in publication ethics and academic values. In line with the results of preliminary observations made by the team, it was noticed that the teachers writing ability can be improved by providing them writing coaching class, including explanations and even training materials that need to be used in scientific writing. This writing coaching class is intended to provide teachers an opportunity to develop their skills, especially skill to write down scientific papers. Writing coaching class will be done by encouraging teachers to compose their ideas, formulating their problems, obtaining references sources, providing consultation rooms, implementing ethics and scientific publishing regulation, and selecting places where scientific papers will be published.